Co-localization of microsomal prostaglandin E synthase-1 with cyclooxygenase-1 in layer II of murine placental syncytiotrophoblasts. (May 2017) - Inagaki, Mai; Nishimura, Tomohiro; Akanuma, Shin-ichi; Nakanishi, Takeo; Tachikawa, Masanori; Tamai, Ikumi; Hosoya, Ken-ichi; Nakashima, Emi; Tomi, Masatoshi
Abstract: The placenta is an organ that secretes prostaglandin (PG) E2 into the fetal-placental circulation to regulate both vascular tone and remodeling of the fetal ductus arteriosus. Placental PGE2 synthesis might be mediated by microsomal PGE synthase-1 (mPGES-1), in addition to cyclooxygenase (COX) isoforms. Thus, the purpose of this study is to clarify the temporal and spatial expression patterns of mPGES-1, together with COX-1 and COX-2, in murine placenta. We found that mPGES-1 and COX-1 protein levels continuously increased in the placental labyrinth from gestational day (GD) 13.5 to GD19.5, becoming higher than in the decidua or the junctional zone by GD17.5. The PGE2 level at GD17.5 was also highest in the labyrinth. Immunofluorescence stainings for mPGES-1 and COX-1 in the labyrinth at GD17.5 overlapped and were located on the fetal side of the signals for connexin 26, which forms gap junctions between maternal-facing (SynT-I) and fetal-facing (SynT-II) syncytiotrophoblast layers, and on the maternal side of the signals for glucose transporter 1 on the basal plasma membrane of SynT-II. On the other hand, the signals for COX-2 did not overlap with those for mPGES-1. These results indicate that COX-1 and mPGES-1 are co-localized in murine placental SynT-II, facing the fetal-placental circulation. Therefore, SynT-II could contribute to placental synthesis of PGE2 for release into the fetal-placental circulation. Highlights: PGE2 is concentrated in murine placental labyrinth. mPGES-1 and COX-1 protein levels continuously increase in the labyrinth. mPGES-1 is co-localized with COX-1 in fetal facing syncytiotrophoblasts (SynT-II). SynT-II could contribute to PGE2 synthesis for release into the fetal circulation.